(untitled) (The Review of Diabetic Studies, 2024)
Aim: This study aimed to evaluate the effectiveness of the Hospital to Home (H2H) initiative on medication adherence, compliance, and quality of life among patients with heart failure. Methods: A true experimental pre-test–post-test control group design was used. A total of 220 heart failure patients were randomly divided into experimental and control groups. The experimental group received the H2H intervention comprising discharge education, counseling, and follow-up for three months. Results: The intervention significantly improved medication adherence, compliance, and functional ability (p ≤ 0.001) in the experimental group compared to the control. Conclusion: The H2H initiative effectively enhanced medication adherence and self-care behavior, promoting better management and outcomes among heart failure patients.